Which Dengue Vaccine Approach Is the Most Promising, and Should We Be Concerned about Enhanced Disease after Vaccination?: Questions Raised by the Development and Implementation of Dengue Vaccines: Example of the Sanofi Pasteur Tetravalent Dengue Vaccine - Guy, Bruno (Cold Spring Harb Perspect Biol, 2018)
Dengue is a still-growing public health concern in many tropical and subtropical regions of the world. The development and implementation of an effective dengue vaccine in these regions is a high priority. This insight focuses on the expected characteristics of a safe and efficacious vaccine, referring to the clinical experience obtained during the development of the first tetravalent dengue vaccine from Sanofi Pasteur, now licensed in several endemic countries. Safety and efficacy data from both short- and long-term follow-up of large-scale efficacy studies will be discussed, as well as the next steps following vaccine introduction.